Estimation of Land and Building Asset Values Using Market and Cost Approaches in Baubau City - Samsul Bahari Bahar; Aswad Asrasal; Muhammad Farhan (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
The community and construction service providers in Baubau City face the problem of problematic work locations, relatively high land prices, a supply chain system that is considered less than ideal, fluctuating construction material price stability, mountainous, undulating and hilly land conditions, and limited availability of supporting work resources, which greatly affect the overall value of building assets. The purpose of this study is to analyze the value of land assets and residential buildings type 60/90 (specification of land area 90 M2 and house building area 60 M2 ) at present and in the coming years, using the market data approach and cost approach methods . Based on the results of the study , it is concluded that : 1) The current value of land assets and house buildings type 60/90 in 2025 is Rp. 325,306,515. 2) The value of house building assets type 60/90 in 2035 or 10 years from now is Rp. 585,551,640.